2000
DOI: 10.1093/intimm/12.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Differential susceptibility of human Th1 versus T h 2 cells to induction of anergy and apoptosis by ECDI/antigen-coupled antigen-presenting cells

Abstract: Antigen-coupled antigen-presenting cells (APC) serve as potent tolerogens for inhibiting immune responses in vivo and in vitro, apparently by providing an antigen-specific signal through the TCR in the absence of co-stimulation. Although this approach has been well studied in rodents, little is known about its effects on human T cells. We evaluated the specificity and mechanisms of tolerization of human T cells in vitro using monocyte-enriched adherent cells that were pulsed with antigen and treated with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…For example, low B7 expression on the donor-coupled cells is necessary for tolerance induction, while CTLA-4 is important for the maintenance phase of Ag-SP tolerance upon secondary encounter with Ag on stimulatory APCs expressing up-regulated levels of costimulatory molecules (14,15,24). Also, we have demonstrated that a chemical fixative, such as ECDI, is required during the coupling process (24,25). Taken together, these observations support the idea that i.v.…”
Section: Discussionsupporting
confidence: 82%
“…For example, low B7 expression on the donor-coupled cells is necessary for tolerance induction, while CTLA-4 is important for the maintenance phase of Ag-SP tolerance upon secondary encounter with Ag on stimulatory APCs expressing up-regulated levels of costimulatory molecules (14,15,24). Also, we have demonstrated that a chemical fixative, such as ECDI, is required during the coupling process (24,25). Taken together, these observations support the idea that i.v.…”
Section: Discussionsupporting
confidence: 82%
“…For this study, our approach was modeled after the insulin-coupled spleen cell tolerance method used to prevent T1D (40). This therapy has direct clinical applications for the treatment of AIP since coupled-cell tolerance has already been used successfully to tolerize Ag-specific human T cell responses (65). The tolerization protocol was successful in limiting the degree of mononuclear cell infiltration into the exocrine pancreas in comparison to SHAM-treated NOD.CD28KO recipient mice.…”
Section: Discussionmentioning
confidence: 99%
“…As apoptosis can follow anergy induction after high dose antigen treatment [37], deletion of allergen-specific Th cells could also lead to in part the reduced proliferative responses seen in our cultures stimulated with high HDM extract concentration. Furthermore, preferential deletion of IL-4- and IL-5-producing T cells could contribute to the shift towards dominant T cell IFN-γ cytokine production.…”
Section: Discussionmentioning
confidence: 99%